Mejoras del proceso productivo a través del análisis y simulación de actividades en la planta industrial de fundición de CEDAL S.A. - Peñafiel Hurtado, Julio César (2020)
The Ecuadorian aluminum factory called Cedal S.A. It is a company dedicated to the manufacture and marketing of extruded aluminum profiles for architectural and structural use for 45 years, its main plant is located at Unidad Nacional Avenue, in Ignacio Flores Parish, Latacunga Canton, Cotopaxi Province. Inside this factory the unique smelting plant of the company is found, which showed the large volume of demand that is requested by the extruders of both Latacunga and Durán the last one located at Guayas province, for this reason the smelting process requires a constant improvement regarding the production rate eliminating downtime and production stoppages, therefore, an activity analysis was carried out through the simulation with ProModel software, detecting optimized transport times and mobile storage that can be better used to increase the existing production rate, when the situation simulation model about the current situation of the plant was developed, it was identified the critical points of the production process where improvements were applied to optimize and standardize the flow of material by increasing the production rate by 8.8% representing a productivity increase of 10 Ton per week which represents an improvement for the production process. According to the results, it is argued that the development of simulation models is a powerful improvement tool, giving competitiveness and development to any kind of industry.